Bacteriophage endolysins — extending their application to tissues and the bloodstream. (April 2021) - Schmelcher, Mathias; Loessner, Martin J
Graphical abstract: Highlights: Endolysins are promising novel therapeutics for treatment of bacterial infections. Endolysins can target infections in different organs and tissues of the human body. They are currently undergoing clinical trials, and first products are available. Systemic application of endolysins is currently hampered by various challenges. Challenges pertain to immunogenicity, pharmacokinetics, and tissue penetration. Abstract : The rapid emergence of antibiotic-resistant bacteria and the lack of novel antibacterial agents pose a serious threat for patients and healthcare systems. Bacteriophage-encoded peptidoglycan hydrolases (endolysins) represent a promising new class of antimicrobials. Over the past two decades, research on these enzymes has evolved from basic in vitro characterization to sophisticated protein engineering approaches, including advanced preclinical and clinical testing. In recent years, increasingly specific animal models have shown efficacy of endolysins against bacterial infections of various different organs and tissues of the body. Despite these advances, some challenges with regard to systemic application of endolysins remain to be addressed. These include immunogenicity, circulation half-life, and cell and tissue-specific targeting and penetration properties.